The assessment of the interaction between base isolation (BI) technique and soil structure interaction (SSI) effects with 3D numerical simulations. (November 2022) - Forcellini, Davide
Abstract: Base Isolation (BI) is a well-known technique that aims to reduce the seismic vulnerability of structures by increasing the structural deformability and the damping. However, these beneficial effects are significantly reduced when the system is founded on deformable soils and then Soil Structure Interaction (SSI) effects are considered. Even if both BI and SSI have been extensively studied in literature, the mutual effects of the two mechanisms are still object of discussion and this paper aims to fill this gap by performing 3D numerical simulations. Several structural systems of different soil conditions are herein modeled in order to account the period elongation and damping increase of the isolated systems. In particular, the paper proposes relationships to calculate these two effects to be used for preliminary estimations avoiding complex and time-consuming analyses. The models have been performed with Opensees to reproduce non-linear hysteretic materials and advanced soil models and consider the non-linear structural performance.